ANALISIS NILAI RATA-RATA DARI SUATU MODEL JARINGAN ANTRIAN TERTUTUP - Susilawati, Cecilia (Jurnal Teknik Elektro, 2003)
In a closed queueing network model it will use mean value analysis to determine the networkthroughput for different value of p, to find the value of p that gives maximum networkthroughput and to indicate the network bottleneck. For certain chosen values of parametersinvolved in this model, it found that the maximum network throughput is 288.1 for p=0.67.The network bottleneck is the fast server. For p>0.67 the fast server is also the networkbottleneck, but when p<0.67, the network bottleneck is the slow server.Keywords: throughput, server, job